Predictive values of baseline matrix metalloproteinase 9 levels in peripheral blood on 3‐month outcomes of high‐risk patients with minor stroke or transient ischemic attack. (11th April 2022) - Zhang, Min; Meng, Xia; Pan, Yuesong; Wang, Yilong; Zhao, Xingquan; Liu, Liping; Li, Jiejie; Yan, Hongyi; Liu, Xiangrong; Zhang, Hui; Pang, Lijuan; Wang, Yongjun
Abstract: Background and purpose: To explore the relationship between baseline levels of matrix metalloproteinase 9 (MMP9) in peripheral blood and the outcomes in patients with acute minor stroke and transient ischemic attack (TIA). Methods: We assessed data from patients with acute minor ischemic stroke or TIA who were included in the CHANCE (Clopidogrel in High‐Risk Patients with Acute Nondisabling Cerebrovascular Events) trial. Baseline level of MMP9 in peripheral blood is classified into five quintiles. We assessed the relationship between the baseline MMP9 and outcomes of stroke recurrence, composite vascular events, and poor functional outcomes within 90 days after stroke onset. Results: Of the 3014 patients included, 295 (9.79%) had recurrent stroke, 289 (9.59%) had recurrent ischemic stroke, 297 (9.85%) had combined vascular events, and 199 (6.64%) had poor functional outcomes within 90 days. We used MMP9 concentrations near hazard ratio (HR) = 1 (Q3) in restricted cubic splines as the reference. The result showed that, compared to patients in the Q3 group, patients in the highest quintile (Q5 group) had an increased risk of poor functional outcomes at 90 days after adjusting the risk factors and confounders ( p  = 0.030), which may be associated with an increased risk of combined vascular events ( p  = 0.052). Using Cox regression models or logistic regression models with restricted cubic spline, we also observed that higher MMP9 ratios were associated with an increased risk of stroke recurrence, combined events, and poor functional outcomes at a range of concentrations. Conclusions: For patients with acute minor stroke or TIA, higher baseline MMP9 level was associated with an increased risk of poor functional outcomes, which might be related to stroke recurrence and combined vascular events. Abstract : For patients with acute minor stroke or transient ischemic attack (TIA), the level of matrix metalloproteinase 9 (MMP9) in peripheral blood should be controlled in a reasonable range, either too high or too low can lead to unfavorable results. Clopidogrel may eliminate the adverse effects of MMP9.